Identification of a Book Owned by Isabella the Catholic: The ‘Smaragdo’ of Cordoba - Martín Barba, José Julio (De Medio Aevo, 2018)
Isabella I of Castile ordered in her last will and testament that all her debts were cancelled with the money outcoming of the sale of her “dresses, jewels and other items of her chamber”. A few days after her death, the executors, by order of the king Ferdinand, started an auction that would prolong for several years, in which numerous buyers acquired most of her belongings, which provoked the permanent dispersion of Isabella’s estate. Regarding the books, nowadays they are few those which are certainly identified as property of the queen. Thanks to the documentation drafted by the royal functionaries during the sale –kept in the General Archive of Simancas–, to some succinct inscriptions located in the front of the first page of the codex and to the magnificent cross of Oviedo located in the back of it, we have could identify, no doubt, that this book belonged to the sovereign.
Keywords: Smaragdus; Homiliary; Florentius of Valeranica; Auction; Isabella I de Castile; Bigarny